Verification of the Nutritional and Dietary Factors Associated with Skeletal Muscle Index in Japanese Patients with Nonalcoholic Fatty Liver Disease - Takashi Himoto; Keiko Miyatake; Takashi Maeba; Tsutomu Masaki (Canadian Journal of Gastroenterology and Hepatology)
We sought to identify the frequencies of presarcopenia, sarcopenia, and sarcopenic obesity in patients with nonalcoholic fatty liver disease (NAFLD) and to cross-sectionally determine the nutritional and dietary factors associated with loss of skeletal muscle mass in such patients. Dietary and body component changes produced by a diet intervention were longitudinally investigated. Forty-six NAFLD patients (24 males and 22 females) were enrolled. A second diet treatment was performed at 6 months after entry in 19 of the enrolled patients (6 males and 13 females). Body compositions and dietary nutrients at six months later were compared with those at entry. Three of the 24 (13%) males and four of the 22 (18%) females fulfilled the criteria for presarcopenia and one (5%) female NAFLD patient was in the criteria for sarcopenia at baseline. None of the patients were in the criteria for sarcopenic obesity. The factors associated with skeletal muscle index in the males were body mass index (BMI), insulin-like growth factor-1, total energy intake, and lipid intake, but only BMI and bone mineral density in females at baseline. The diet intervention decreased the skeletal muscle mass in the 6 males by decreasing the total energy intake via lower protein and lipid intakes and improved their liver dysfunction. In the 13 females, a decrease in total energy intake via lower carbohydrate and lipid intake did not change the skeletal muscle mass. These results suggest that loss of skeletal muscle mass is frequently observed in nonobese NAFLD patients and that the frequency of sarcopenic obesity seems to be rare in NAFLD patients. The nutritional and dietary factors that regulate loss of skeletal muscle mass were distinct between our male and female NAFLD patients. Thus, the skeletal muscle mass of such patients as well as their body weight and liver function should be monitored during diet interventions.